تاثير المبيد سابيرمثرين على المجتمع الحيوي في تربه رمليه مزيجيه - عبد الزهرة ابتسام (University of Thi-Qar Journal of Science, 2010)
A study of the effect of the insecticide cypermethrin has been studied on population counts of bacteria , fungi , Azotobacter and nitrogenase activity on loamy sand soil. The soil characterized by low value of catione and organic mater .Bulk density and the percentage of sand were high .The insecticide was added to soil in three concentration (0.004, 0.008 ,0.012)mg /L assigned as (T1,T2,T3) respectively .The concentration of insecticide and the incubation time (7, 14, 21) day was significantly affected (p<0.01) bacteria ,fungi and Azoyobacter density, but there was no significantly inhibitory effect of the concentration and incubation time on nitrogenase activity.